DAMPAK KOMPENSASI KENAIKAN HARGA BBM TERHADAP KEMISKINAN DI INDONESIA - Akhmad, Akhmad (Academica, 2014)
The study aims to determine the compensation for the impact of fuel priceincreases on poverty in Indonesia. This study uses data from the CentralStatistics Agency (BPS), the Ministry of Development Planning/Bappenas,BPH Migas, and several other sources. Data was analyzed using descriptiveanalysis. The results show that the increase in fuel prices coupled with thecompensation program is not entirely successful in avoiding increasing poorpopulation by 480 thousand inhabitants in September of 2013. If it is assumedthat the government aims to reduce all the poverty of impact of fuel price hike,it can be said that the effectiveness of the program MLSM and other programsis not fully succeed although three can not also be said to fail. Some reasonsineffectiveness of the program is strongly associated with how the governmentpredicting the impact of rising fuel prices and how governments preparingtheir responsiveness. With the high irregularities in the distribution of fuelcompensation fund , this indicates that the compensation program has not beenfully carried out by the government-planned and structured. This is evidenceby the number of complaints from the public. Therefore, it is necessary toidentify and scope of good supervision, so that other compensation programsthat will be implemented by the government in the future will be moresuccessful, and the goal to reduce poverty can be achieved .Keywords : Fuel Price Increases, Compensation Program, Poverty